PENANAMAN NILAI-NILAI MORALITAS PADA ANAK DINI USIA (STUDI KASUS PADA SEBUAH LEMBAGA PENDIDIKAN TK DI SEMARANG) (Faculty of Social Science, Universitas Negeri Semarang, 2010)
The most important agenda in the recent time is the problem of morals education. It says importantbecause there are some problems who relate the student, such as student clash. So that the conditionshave to minimalize by construction of students morals. One of all effort is the implantation of moralvalues from early childhood. The implantation of moral values are effort which are still needed to formedyoung generation would have the good moral values. School is one of all place for its effort. Thereforethis research tried to describe the teachers’ efforts in the process of moral value implantation in onekindergarten in Semarang. Based on the description above, problem of research can be formulated: (1)what kind of situations, the teacher of kindergarten carry out the construction of morals to the children,(2) How’s the process of the construction of moral values to the children. Based on the focus of problemof research, the aim of research can be formulated: (1) to know the kind of situations, the teacher ofkindergarten carry out the construction of morals to the children, and (2) to know the process of theconstruction of moral value to the children. This research employed the qualitative approach. With thisapproach, it was expected that a clear description of the meaning of the reality would be obtained. Thesubject of research is the children of Pembina Kindergarten Semarang. The kindergarten have to chooseas the location of research because the status of the kindergarten is state kindergarten which have standardprocedure, so that the fi nding of research can be used as the matter of judgement by the others to carryout the construction of morals to the students. The data were collected through observation, interviews,and documentation. The data analyses in this study covered the domain, componential, taxonomy, andthematic analyses. Based on the fi ndings of the research, it can be conclude that, fi rst, the constructionof the moral values to the children had to applicated by the cultural and behavioral model approach withthree ways, e.g: planting a good discipline, etiquette, and love and affection, in the teaching learningprocess and behavioral model, and secondly, in the construction of moral values to the children, theteachers applicated classically and advice the child when found deviated from traditional custom, suchas, child who like kissing, girliest, etc. From the fi ndings of research above, it can be suggested that theteachers have to concern of all thems behavior in school, because it can be easily and faster imitate allword and appearance of the teachers.Keywords: implantation, moral values, early childhood